Tábua de vida da população feminina de Ribeirão Preto, SP (Brasil), 1973 Life table for the female population of the county of Ribeirão Preto (State of S. Paulo, Brazil), 1973 - Clarisse D. G. Carvalheiro (Revista de Saúde Pública, 1977)
Obteve-se a tábua de vida corrente, para a população feminina do Município de Ribeirão Preto, SP, Brasil, no ano de 1973. A curva de sobreviventes em idades sucessivas e a esperança de vida foram comparadas com valores obtidos para 1950, no mesmo Município. A esperança de vida ao nascer, 65,3 anos foi comparada com as obtidas para diferentes regiões do Estado de São Paulo em 1967, população feminina do Rio Grande do Norte (40,0 anos), do Rio Grande do Sul (62,5 anos) e do Brasil (55,6 anos) em 1970. The life table for the female population of the county of Ribeirão Preto (State of S. Paulo, Brazil), in the mid-year 1973, was constructed. The curve of survivors at successive ages and expectation of life at birth were compared with the values obtained by Duarte & Milanesi (1958) for 1950, for the same county. Expectation of life at birth, 65,3 years, was compared also with the values obtained for different regions of the State of S. Paulo in 1967, female population of the State of Rio Grande do Norte (40,0 years), of the State of Rio Grande do Sul (62,5 years) and Brazil as a whole (55,6 years) in 1970.